Affect at work - the impact of emotion regulation on employees' well-being, proactive and adaptive performance - Schraub, Eva Maria (2011)
This dissertation addresses intra- and interpersonal effects of emotion regulation on contextual work performance. Based on a comprehensive framework that was deducted from theories on affect and organizational behavior, four empirical studies in applied settings address the question of how emotion regulation at work affects well-being as well as proactive and adaptive performance. The studies examine different forms of emotion regulation (intra- and interpersonal regulation, habitual and situational regulation) and their intra- and interpersonal effects. They rely on cross-sectional and longitudinal surveys that partly use a multilevel approach. A pre-study examines direct relationships between self-rated habitual intrapersonal emotion regulation strategies at work (expressive suppression, reappraisal) and supervisor-ratings of individuals‘ adaptive and proactive performance in an explorative way. Hierarchical multiple regression analyses of data from a cross-sectional work sample (N = 83) indicate that the habitual use of expressive suppression is inversely related and the habitual use of reappraisal is not significantly related to the ratings of proactive and adaptive performance. Study 1 analyzes how the situational application of intrapersonal emotion regulation strategies (expressive suppression, reappraisal) impacts the effects of negative emotional work experiences on individuals‘ recovery and well-being. Multilevel analyses of repeated-measurement data from a two-week diary of a student sample (N participants = 63, N data = 726) reveal that both reappraisal and expressive suppression buffer prolonged adverse effects of negative emotional experiences. Study 2 addresses the joint impact of perceived changes and habitual intrapersonal emotion regulation at work (expressive suppression) on individuals‘ self-rated well-being and adaptive performance. Bootstrapping analyses of cross-sectional data from a work sample (N = 153) show that negative effects of change on both criteria are buffered if employees do not fully express their emotions at work. Study 3 focuses on the impact of team conflict and of leaders‘ emotion management on employees‘ well-being and proactive performance. Multilevel analyses on longitudinal data from 59 work teams indicate that task conflict (rated by team members) is detrimental for team members‘ positive affect (self-rated) and, thereby, for their proactive performance (rated by a colleague). Leader emotion management (rated by team members), in contrast, positively impacts team members‘ positive affect and their proactive performance. The study further shows that the better the team leaders‘ emotion management, the lower the relationship conflict (rated by team members) in their teams. The dissertation provides a comprehensive and yet differentiated contribution on different forms and consequences of emotion regulation at work and considers its dynamic nature. Addressing relations that are of relevance for understanding organizational behavior, but that have rather been neglected by previous research, it extends the literature on both emotion regulation and work performance.
Keywords: Hochschulschrift